Assessment of Satisfaction level of Admitted patients in a Trauma Care Centre of Tripura - A Questionnaire Based Study - Samarpita Dutta; Bidhan Goswami; Bhaskar Bhattacharjee; Shauli Sengupta (Indian Association of Preventive and Social Medicine, 2023)
Introduction: Tertiary care hospitals deal with complex medical care and are the face of development of the healthcare delivery system. Towards this advancement, good quality of patient care services addsvalue. One of the ways to ind out about the quality of ongoing services is by carrying out patient satisfaction surveys. In this context, nearly ive years after the inauguration of the state's irst ever trauma care centre, it was planned to take a feedback on the services provided by the centre. Objective: To assess the level of satisfaction of the patients treated in the trauma care center of a tertiary care hospital in the state of Tripura. Method: A total of three hundred and sixty ive (365) patients admitted in the trauma care centre were interviewed using a validated questionnaire adapted from National Health System survey format. Data was collected over period of six months. For the irst three months, interviews were conducted on all odd days of the week and for the next three months the interviews were conducted on even days of the week. Results: In the present study, 84% of the responders were male and 16% female. It was observed that 78.08% of the patients had full conidence and trust on the doctors who attended the patients. The overall ranking provided by the patients on the services received in the hospital was satisfactory. In this study, 78.9% and 10.7% of the patients have rated the services to be 'good' and 'excellent', respectively. Conclusion: Although most of the patients were satisied with the services provided in the trauma care centre of the study, 9.6% of them also reported that there is need to improve services. This study will not only help the hospital management to implement new policies but also prepare the hospital well to meet the needs of patients admitted in the trauma care center